Expression and Cleavage of Middle East Respiratory Syndrome Coronavirus nsp3-4 Polyprotein Induce the Formation of Double-Membrane Vesicles That Mimic Those Associated with Coronaviral RNA Replication - Diede Oudshoorn; Kevin Rijs; Ronald W. A. L. Limpens; Kevin Groen; Abraham J. Koster; Eric J. Snijder; Marjolein Kikkert; Montserrat Bárcena (mBio, 2017)
ABSTRACT Betacoronaviruses, such as Middle East respiratory syndrome coronavirus (MERS-CoV), are important pathogens causing potentially lethal infections in humans and animals. Coronavirus RNA synthesis is thought to be associated with replication organelles (ROs) consisting of modified endoplasmic reticulum (ER) membranes. These are transformed into double-membrane vesicles (DMVs) containing viral double-stranded RNA and into other membranous elements such as convoluted membranes, together forming a reticulovesicular network. Previous evidence suggested that the nonstructural proteins (nsp’s) 3, 4, and 6 of the severe acute respiratory syndrome coronavirus (SARS-CoV), which contain transmembrane domains, would all be required for DMV formation. We have now expressed MERS-CoV replicase self-cleaving polyprotein fragments encompassing nsp3-4 or nsp3-6, as well as coexpressed nsp3 and nsp4 of either MERS-CoV or SARS-CoV, to characterize the membrane structures induced. Using electron tomography, we demonstrate that for both MERS-CoV and SARS-CoV coexpression of nsp3 and nsp4 is required and sufficient to induce DMVs. Coexpression of MERS-CoV nsp3 and nsp4 either as individual proteins or as a self-cleaving nsp3-4 precursor resulted in very similar DMVs, and in both setups we observed proliferation of zippered ER that appeared to wrap into nascent DMVs. Moreover, when inactivating nsp3-4 polyprotein cleavage by mutagenesis, we established that cleavage of the nsp3/nsp4 junction is essential for MERS-CoV DMV formation. Addition of the third MERS-CoV transmembrane protein, nsp6, did not noticeably affect DMV formation. These findings provide important insight into the biogenesis of coronavirus DMVs, establish strong similarities with other nidoviruses (specifically, the arteriviruses), and highlight possible general principles in viral DMV formation. IMPORTANCE The RNA replication of positive stranded RNA viruses of eukaryotes is thought to take place at cytoplasmic membranous replication organelles (ROs). Double-membrane vesicles are a prominent type of viral ROs. They are induced by coronaviruses, such as SARS-CoV and MERS-CoV, as well as by a number of other important pathogens, yet little is known about their biogenesis. In this study, we explored the viral protein requirements for the formation of MERS-CoV- and SARS-CoV-induced DMVs and established that coexpression of two of the three transmembrane subunits of the coronavirus replicase polyprotein, nonstructural proteins (nsp’s) 3 and 4, is required and sufficient to induce DMV formation. Moreover, release of nsp3 and nsp4 from the polyprotein by proteolytic maturation is essential for this process. These findings provide a strong basis for further research on the biogenesis and functionality of coronavirus ROs and may point to more general principles of viral DMV formation.